Real-life efficacy and safety of ingenol mebutate for the treatment of actinic keratosis of the face and scalp: A single arm retrospective study. (1st November 2016) - Ricci, Francesco; Tambone, Sara; Neri, Luca; Fania, Luca; Piccioni, Antonella; Guerriero, Cristina; Fargnoli, Maria Concetta; Peris, Ketty
Abstract: Background : The efficacy and safety of ingenol mebutate versus placebo have been proven in four randomized controlled trials (RCTs), although there is a lack of real-life studies corroborating such promises in routine clinical practices. In our study, we sought to describe real-life effectiveness, safety and regimen adherence among patients with multiple AKs on the face treated with ingenol mebutate and evaluate correlates of clinical outcomes in this population.Methods : We reviewed the clinical charts of adult patients with multiple (≥3) AK grade I and II of the face and scalp, treated with ingenol mebutate from April 2014 to April 2015. All subjects received the medication according to ingenol mebutate standard of care.Results : We enrolled 88 patients during the study period and carried out 122 treatment cycles. The unadjusted lesion clearance rate per treated field was 81.3% and the average local skin reactions score at day 4 was 6.0 ± 2.8 (range: 0–18).Conclusions : We observed an excellent rate (>99%) of adherence to ingenol mebutate. This was mirrored by the fact that our clinical outcomes broadly confirmed results obtained in RTCs. Our study showed that the efficacy and safety of ingenol mebutate observed in RCTs can be reliably translated in real-world practice.